Teknik Konservasi Tanah serta Implementasinya pada Lahan Terdegradasi dalam Kawasan Hutan - Wahyudi Wahyudi (Teknik Lingkungan Universitas Islam Indonesia, 2014)
Large of degraded forest areas in Indonesia namely 19.5 million ha and its rate start from 1.8 to 2.84 million ha years-1. Initially in the form of virgin forests, they were degraded become low potential forest, scrub, bush, grass land to critical land. The critical land is very dangerous for natural resources establishment because happened the high erosion and menacing flood. The solutions to minimize the environmental damage in the critical land are developing the soil conservation technique in the sites. This research was aimed to collect and analyze some soil conservation techniques and its implementation in the degraded land of forest regions. The research was conducted with literature and fields study in the PT. Gunung Meranti areas, Kapuas District, Central Kalimantan Province. Some soil conservation techniques that applied in the degraded land of forest regions are wet masonry, stone terrace works, gabion works,log retaining works,log grib works,bamboo and wicker terrace, soil bag terrace works and straw mat terrace works. To support the civil and vegetation soil conservation technique, commonly using the water channels as sod water channel works, stone water channel works, soil bag water channel works and catchment pipe culvert.